Early Onset of Ocular Neovascularization After Hyperbaric Oxygen Therapy in a Patient With Central Retinal Artery Occlusion. Issue 2 (December 2016) - Tang, Peter; Engel, Kevin; Parke, David
Abstract Central retinal artery occlusion (CRAO) is an infarction to the retina that results in acute, frequently severe vision loss. Long-term complications such as ocular neovascularization (ONV) can occur and result in neovascular glaucoma and vitreous hemorrhage. Recent studies have explored acute hyperbaric oxygen (HBO) therapy as a promising treatment for CRAO to improve long-term vision potential; however, its effects on CRAO complications have not been well characterized. This study was conducted to better characterize the effects of HBO therapy on complications from CRAO. We present a unique case of ONV in an eye within 1 month after successfully completing acute HBO therapy for a CRAO, highlighting the importance of routine monitoring in this unique population.